MemoryScan: Smart Digital Transformation of Large-scale Environments for Eliciting Location Specific Knowledge - Michlowitz, Robert A.; Kider, Joseph T.; Walters, Lori C. (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
MemoryScan is a prototype community-scale virtual environment platform to elicit memory recall from current and former citizens and visitors of a selected municipality. Gathering recollections on a continuous community scale enables location-based stories to be visually tied together rather than existing as locationally independent reflections. The interdisciplinary project team will examine the potential advantages of using a spatially realistic virtual environment to assist in the capture of participant reflections and collect supporting privately held documents. Designed as a large 3D photorealistic environment, MemoryScan will use an eXtended reality (XR) Head-Mounted Display (HMD) or PC interface to permit the capture of oral reflections of a community's heritage with remote participant access. Should this project's experimental testing validate this view, the fully developed system will be made available to crowdsource information on a national scale. This system would benefit historians, anthropologists, political scientists, city planners, and others.